Analisis Kestabilan Lereng Berdasarkan Data Sifat Fisik dan Mekanik pada Lereng Batuan di Jembatan Merah Punggawa D’Emba Kabupaten Gowa - Arsdin, Dian Dwi Apriliyani; Syarifullah Bundang; Sumantri, Alifianty Delila Imani; Minarti; Putri, Nilam Sry (Universitas Islam Negeri Alauddin Makassar, 2025)
Slope stability analysis is essential to ensure human survival and serves as the basis for disaster mitigation and land-based spatial planning. One area with high landslide potential is the Jeneberang watershed, as evidenced by its frequent landslide history. The stability parameter of a slope is the Safety Factor (FK). The purpose of this study is to analyze the slope stability at the Punggawa D'Emba Red Bridge, Gowa Regency. The methods used in this study include analysis of the types of physical and mechanical properties of the rocks that make up the slope, analyzing the type of landslide using kinematic analysis and analysis of the Safety Factor value of Slide using Rocscience 6.0 Software. The results of this study indicate that if a landslide occurs, the type of landslide that occurs at the research location is a planar landslide type, a slope gradient of 52° and a Safety Factor value of 5.2. The slope at the study location shows a high slope Safety Factor value, this means that the slope is declared stable.